Design of a spectrofluorometric method for the determination of ethanol in air - Alfaro Solís, Rosa (2013)
A simple and rapid method for the determination of ethanol in air was designed, using a chilled glass spiral for sampling and a flow injection system coupled to a column containing alcohol oxidase, immobilized on glass beads and a fluorescence detection system for analysis. We evaluated the excitation wavelength (310 nm) and the emission wavelength (410 nm), the flow of the mobile phase (1,05 mL min-1), the length of the reactor (1,00 m), the length (7,00 cm) and the diameter (3,0 mm) of glass column containing alcohol oxidase and the concentration of sodium hydroxide solution (0,15 M). The analytical method was linear from 1,00 μmol L-1 to 5,00 μmol L-1 ethanol. We obtained a correlation coefficient of 0,995, a repeatability of 0,8 %, a limit of detection and quantification of 0,350 μmol L-1 and 0,670 μmol L-1, respectively. The methodology was evaluated in field sampled and the ethanol concentrations in air ranged from 0,356 ± 0,001 mg/m3 and 1200 ±2 mg/m3. These concentrations did not exceed the maximum allowable limit of 1884 mg/m3, according to OSHA.